Understanding the Stock Market's Response to Monetary Policy Shocks - Johann Scharler (Oesterreichische Nationalbank (OeNB), 2004)
This paper explores whether a limited participation model of the monetary transmission mechanism can account for the observed response of stock market returns to monetary policy shocks. It is found that the model generates responses that broadly match the empirical counterparts, although the magnitudes are somewhat too small. Moreover, the results suggest that the increased exposure of bank-dependent firms to liquidity shocks cannot fully account for the heterogenous responses of returns that are observed across firms.
Keywords: E4; E5; G1; 330; limited participation; asset pricing; stock market